Biological and clinical significance of loss of heterozygosity at the INPP4B gene locus in Japanese breast cancer. (February 2016) - Tokunaga, Eriko; Yamashita, Nami; Kitao, Hiroyuki; Tanaka, Kimihiro; Taketani, Kenji; Inoue, Yuka; Saeki, Hiroshi; Oki, Eiji; Oda, Yoshinao; Maehara, Yoshihiko
Abstract: Purpose: INPP4B is considered to function as a putative tumor suppressor through its inhibitory function of Akt. In various malignant tumors, loss of heterozygosity (LOH) at the chromosomal region containing INPP4B and lower expression of INPP4B has been reported. The purpose of this study was to examine the frequency of the INPP4B LOH and its association with the clinicopathological characteristics and prognosis in breast cancer of Japanese women. Methods: The allelic alteration at the INPP4B and PTEN gene loci was analyzed in 277 invasive primary breast carcinomas. The relationships between INPP4B LOH and the clinicopathological features were investigated. Results: Among the 238 informative cases for the evaluation, LOH at the INPP4B gene locus was observed in 43 tumors (18.1%). INPP4B LOH was significantly correlated with ER and PR negativity (p = 0.0009 and p = 0.0029, respectively), higher nuclear grade (p < 0.0001), higher Ki67 labeling index (p = 0.0006), triple-negative (TN) subtype (p = 0.0005) and PTEN LOH (p < 0.0001). INPP4B LOH was significantly associated with poorer prognosis, in terms of the relapse-free survival (RFS) and overall survival (OS). According to the multivariate analyses, INPP4B LOH was not independently associated with the prognosis. Conclusion: The incidence of INPP4B LOH was significantly higher in the TN subtype and positively correlated with PTEN LOH. INPP4B LOH was associated with more aggressive and proliferative phenotype. INPP4B LOH was also associated with poorer prognosis. Highlights: INPP4B is considered to function as a tumor suppressor. This study examined the INPP4B loss of heterozygosity (LOH) in breast cancer. INPP4B LOH was significantly correlated with triple-negative subtype and PTEN LOH. INPP4B LOH was significantly associated with poor prognosis.